Systematic review of factors influencing the demand for medical and health insurance in Malaysia - Ellyana Mohamad Selamat; Siti Rasidah Abd Ghani; Nurcholisah Fitra (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction Medical and health insurance provides financial protection against the consequences of the occurrences of health risks. Different perceptions have led to resistance to change, as well as the acceptance level from Malaysians. It is fundamental to study the reception and acceptance of all types of insurance schemes by Malaysians and to identify the knowledge and information pertaining to reception by Malaysians. Methods A systematic search was performed from six major search engines from 2013–2018 in searches of published articles on factors that influence the demand or willingness to pay for health insurance among Malaysians. There were nine articles included, in which personal factor was found to influence the most when demanding for health insurance. Results Higher education level, younger age group, and good knowledge were associated with higher demand for health insurance. Higher household monthly income and the cost to pay were among the positively significant economic determinant factors to demand for medical insurance. Conclusions Education and promotion are important to understand why such policies were introduced and how they intend to serve the public before implementing major policies. These elements capture the essence of ‘health promotion’, which is about enabling people to take control over their health and thereby, improving their health.